Religion and violence : philosophical perspectives from Kant to Derrida - Vries, Hent de (Johns Hopkins University Press, 2001)
Does violence inevitably shadow our ethico-political engagements and decisions, including our understandings of identity, whether collective or individual? Questions that touch upon ethics and politics can greatly benefit from being rephrased in terms borrowed from the arsenal of religious and theological figures, because the association of such figures with a certain violence keeps moralism, whether in the form of fideism or humanism, at bay. De Vries' posing of such questions and rearticulations pioneers new modalities for systematic engagement with religion and philosophy alike.